HEPATITIS C-A RISK FACTOR FOR GALLSTONE DISEASE - Shah, Syed Inamullah; Shah, Sajida; Hannan, Abdul (Journal of Ayub Medical College Abbottabad, 2014)
Background: There is increasing evidence that chronic liver disease is one of the risk factors for gallstone disease. A few published studies have documented the link between Hepatitis C Virus (HCV) related chronic liver disease and increased incidence of gallstones but these studies did not exclude subjects with other risk factors like cirrhosis. This study aimed to establish an association between HCV infection and gallstones by excluding subjects with all other risk factors for gallstones. Methods: This cross sectional study was carried out at four hospitals of Rawalpindi, Pakistan, over a period of 18 months. It included all cases referred for ultrasound scan of abdomen. A total of 2000 cases, were included in the study by consecutive, non-probability sampling. Anti-HCV antibody test was carried out in all subjects by ELISA and sonography was done to determine presence or absence of gallstones. Results: Patients suffering from HCV had a significantly high percentage of gallstones as compared to seronegative subjects (p=0.001). In seropositive group, more males had gallstones (p=<0.001) and prevalence of gallstones was significantly high in younger population with age at or below 40 years (p=<0.001). Conclusion: Risk of gallstone disease is increased in patients suffering from HCV infection. This association is more pronounced in males. Keywords: Hepatitis C, Gallstones, Cholelithiasis